New insights for the regulatory feedback loop between type 1 crustacean female sex hormone (CFSH-1) and insulin-like androgenic gland hormone (IAG) in the Chinese mitten crab (Eriocheir sinensis) - Zhu, Dandan; Feng, Tianyi; Mo, Nan; Han, Rui; Lu, Wentao; Shao, Shucheng; Cui, Zhaoxia (Frontiers in Physiology, 2022)
To clarify the hormone control on sex determination and differentiation, we studied the Chinese mitten crab, Eriocheir sinensis (Henri Milne Edwards, 1854), a species with importantly economic and ecological significance. The crustacean female sex hormone (CFSH) and the insulin-like androgenic gland hormone (IAG) has been found to be related to the sex determination and/or differentiation. CFSH-1 of E. sinensis (EsCFSH-1) encoded a 227 amino-acid protein including a signal peptide, a CFSH-precursor-related peptide, and a mature CFSH peptide. Normally, EsCFSH-1 was highly expressed in the female eyestalk ganglion of an adult crab, while the expression was declined in the intersex crabs (genetic females). The intersex crabs had the androgenic glands, and the EsIAG expression was close to the level of the normal males. During the embryogenesis and larval development, the changes of EsCFSH-1 and EsIAG genes expression in male and female individuals was shown after the zoea IV stage. Next, we confirmed the existence of the regulatory feedback loop between EsCFSH-1 and EsIAG by RNA interference experiment. The feminization function of EsCFSH-1 was further verified by examining the morphological change of external reproductive organs after EsCFSH-1 knockdown. The findings of this study reveal that the regulatory interplay between CFSH and IAG might play a pivotal role in the process of sex determination and/or differentiation in decapod crustaceans.